Study of Productive, Reproductive and Morphological Traits of Bucks in Different Eco-zones of Lumbini Province, Nepal - Dahal, M; Azad, MH (Nepalese Veterinary Journal, 2023)
Goat is a domesticated small ruminant, primarily reared by small farmers for meat production, across the country. The productivity of goat is often low, which could be related to several genetic and non-genetic factors. A field study was carried out to characterize, evaluate and estimate the effect of non-genetic factors on the productive and reproductive performance of hill goats in different eco- zones at Rolpa district of Lumbini province. Altogether 43 bucks of different age groups were identified for this study. Morphological attributes, productive, and reproductive performance were collected based on field monitoring and measurements within different altitudes of Rolpa district. Least square analysis was performed using Harvey (1990) computer software package, and means were compared using DMRT. The measurements of morphological traits were higher in male as compared to females. Results revealed the age at first service of bucks (336 days), the average body weight of buck was (38.76 kg), the overall body length of buck from one to four year was 78.01±0.35 cm, overall heart girth of one to four years’ age buck was 77.57±1.65 cm, average wither height from one to four-year-old buck was 71.88±2.13 cm, overall average Scrotal circumference of bucks (1-4 years) were 24.38±0.71 cm respectively. The results of this study suggest that the performance of low altitude goat flocks was better than mid and high-altitude goat flocks in the Rolpa district in terms of production and reproduction traits. The selection of the best performance of buck could be done on the basis of their traits for breeding. This result could be attributed to superior genotype along with better management practices followed by the farmers in Rolpa district.